2016
DOI: 10.1155/2016/5302069
|View full text |Cite
|
Sign up to set email alerts
|

Maraviroc-Mediated Lung Protection following Trauma-Hemorrhagic Shock

Abstract: Objectives. The peroxisome proliferator-activated receptor gamma (PPARγ) pathway exerts anti-inflammatory effects in response to injury. Maraviroc has been shown to have potent anti-inflammatory effects. The aim of this study was to investigate whether PPARγ plays an important role in maraviroc-mediated lung protection following trauma-hemorrhage. Methods. Male Sprague-Dawley rats underwent trauma-hemorrhage (mean blood pressure maintained at approximately 35–40 mmHg for 90 minutes), followed by fluid resuscit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Severe trauma with hemorrhagic shock, as modeled here in mice, can lead to rapid lung injury and dysfunction [ 57 , 58 ]. To assess the impact of the IL33/ILC2/IL5/neutrophil pathway on lung changes 6 hours after HS/T in mice lacking IL33 or ILC2 or in which IL5 had been neutralized ( Fig 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Severe trauma with hemorrhagic shock, as modeled here in mice, can lead to rapid lung injury and dysfunction [ 57 , 58 ]. To assess the impact of the IL33/ILC2/IL5/neutrophil pathway on lung changes 6 hours after HS/T in mice lacking IL33 or ILC2 or in which IL5 had been neutralized ( Fig 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been observed that MVC decreases mucosal inflammation (30), VCAM-1 (31), T cell infiltration, neuroinflammation (32) and endothelial dysfunction (33). Regarding the lung, a model of induced hemorrhagic shock in rats reported that MVC has a protective role against pulmonary damage (34). All the aforementioned, along with the broad safety range of MVC, good tolerance an low incidence of adverse effects (35) makes it an excellent candidate to be used as a modulator of the dysregulated immune response in COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Based on its complex pathophysiological mechanisms, the interaction of various factors, such as in ammatory damage [2,3]. and blood-brain barrier destruction, [4].…”
Section: Introdutionmentioning
confidence: 99%
“…Acute ischemic stroke is the most common cerebrovascular event with high morbidity and mortality[1].. Based on its complex pathophysiological mechanisms, the interaction of various factors, such as in ammatory damage [2,3]. and blood-brain barrier destruction, [4].…”
Section: Introdutionmentioning
confidence: 99%
See 1 more Smart Citation